2002
DOI: 10.1037/0735-7028.33.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Ethical ambiguities in the practice of child clinical psychology.

Abstract: This article presents results from a survey of ethical beliefs about practice dilemmas unique to clinical work with children and adolescents. Survey data suggest that identical practices are not always ethically equivalent, particularly when the developmental status of the client is varied. The survey also reveals widespread ambiguity about what constitutes ethical practice, as manifested both in individual uncertainty and in the absence of group consensus. Ethically guided clinical practice is presented as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…When these results are considered along with previous research suggesting that therapists' ethical beliefs may depend upon the point in time or geographic region in which they were measured (Tubbs & Pomerantz, 2001) or the developmental status of a client (Mannheim et al, 2002), they suggest that psychologists' ethical beliefs regarding therapist practices may in fact be situational rather than constant.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…When these results are considered along with previous research suggesting that therapists' ethical beliefs may depend upon the point in time or geographic region in which they were measured (Tubbs & Pomerantz, 2001) or the developmental status of a client (Mannheim et al, 2002), they suggest that psychologists' ethical beliefs regarding therapist practices may in fact be situational rather than constant.…”
Section: Discussionmentioning
confidence: 71%
“…In fact, a review of the literature reveals only one study of therapist ethics (which used a different method than that of Pope et al) in which defined and varied client characteristics were considered. This study concluded that the ethical beliefs of Minnesota psychologists regarding clinical work with children and adolescents depended upon the developmental status of the client in question (Mannheim et al, 2002).…”
mentioning
confidence: 98%
“…Will it be based on the principle of the act "which makes for the best whole, in the sense of awakening the least sum of dissatisfactions" (James, 1899(James, /1994. Mannheim et al (2002) surveyed a large number of psychologists in the U.S. about practice dilemmas when working with children and adolescents. The survey did not find consensus about what constitutes ethical practice and found much uncertainty among individual practitioners.…”
Section: Mapsmentioning
confidence: 99%
“…Dečiji klinički psiholozi, koji rade sa decom sa "normalnim" ili sa posebnim potrebama, najveće probleme imaju sa: a) čuvanjem određenih tajni od roditelja 9 , b) pribavljanjem validne saglasnosti i c) prelaženjem određenih granica, koje iniciraju njihovi klijenti (Mannheim et al, 2002). Oni koji rade sa zavisnicima od psihoaktivnih supstanci suočavaju se sa različitim problemima vezanim za poverljivost i odnose sa porodicom pacijenata, ali i sa mnogo važnijim pitanjem autonomije klijenata.…”
Section: Etička Pitanja U Praksi Kliničkih Psihologaunclassified